2011
DOI: 10.1093/infdis/jir129
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Measles in Africa

Abstract: During 2002-2009, the median age of confirmed measles was 36 months. In countries with ≥50% aMCV1 coverage compared with low-coverage countries, age shifted to older children and young adults; for infants, age decreased slightly with higher coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 28 publications
9
51
1
Order By: Relevance
“…[14][15][16][17][18][19] In comparison with other studies, the mean age of occurrence is similar in our study (Goodson et al 2005). The occurrence in unimmunized or partially immunized population is also comparable with other studies (Valinga J. et al) The incidence of complications in our study was 1.19% which is less when compared to other studies.…”
Section: Graph 6: Distribution Of Complicated Measles Casessupporting
confidence: 88%
“…[14][15][16][17][18][19] In comparison with other studies, the mean age of occurrence is similar in our study (Goodson et al 2005). The occurrence in unimmunized or partially immunized population is also comparable with other studies (Valinga J. et al) The incidence of complications in our study was 1.19% which is less when compared to other studies.…”
Section: Graph 6: Distribution Of Complicated Measles Casessupporting
confidence: 88%
“…Research in India during a measles epidemic in 2011 showed a higher rate of illness in a rural area (the village of Gorkhi with 44/1000) in comparison with an urban area (27/1000) (26). On the basis of data collected in 40 African countries in 2002-2009, it was found that 33% of the patients came from urban areas and 67% from rural areas (27).…”
Section: Discussionmentioning
confidence: 99%
“…Following wide application of measles vaccination, measles has been controlled in China and in other countries [17][18][19] Most of the clinical parameters, such as fever, rashes, eruption, typical catarr, cough symptoms, and Koplik spot were found among measles patients. Measles virus would weaken immune systems, and thus made people infected with the virus much more susceptible to opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%